The role of the Government in regulating the use of electronic payment methods Under the vision of the Kingdom of Saudi Arabia 2030 - Mohamed, Lobna Ahmed Mousa (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aimed to clarify the regulatory and organizational role of the state of using Electronic Payment Methods, and the ability of Saudi Economy to accept the Digital Money in transactions. In addition, examining the regulatory and organizational procedures taken by the Kingdom to protect the national economy in the light of these transactions, especially the Money Laundering Issues. The questionnaire method was relied upon by withdrawing a sample from the research community, which represented 32% of the research community. The data and assumptions were analyzed by using the Statistical Package for Social Science program (SPSS -20). The research found that, there is an importance of using electronic payment methods in Saudi Economy, and there is an acceptance of using Digital Money in electronic transactions, but with a degree of precaution. Finally, the regulatory and organizational authorities have the procedures and tools to protect the national economy from the negative use of electronic payment methods specially, Money Laundering Operations.